2014
DOI: 10.1186/1471-2350-15-5
|View full text |Cite
|
Sign up to set email alerts
|

CCL3L1 copy number, CCR5genotype and susceptibility to tuberculosis

Abstract: BackgroundTuberculosis is a major infectious disease and functional studies have provided evidence that both the chemokine MIP-1α and its receptor CCR5 play a role in susceptibility to TB. Thus by measuring copy number variation of CCL3L1, one of the genes that encode MIP-1α, and genotyping a functional promoter polymorphism -2459A > G in CCR5 (rs1799987) we investigate the influence of MIP-1α and CCR5, independently and combined, in susceptibility to clinically active TB in three populations, a Peruvian popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 44 publications
(50 reference statements)
0
14
0
Order By: Relevance
“…It suggested that the CNV was an independent risk factor for pulmonary TB in contrast with SNPs among Chinese Uygurs. However, a recent study found that there was an association of CCL3L1 copy number with TB in a northwestern Colombian population [ 31 ], but not in African and Peruvian populations [ 32 ]. All these data indicate that CNVs in some special genes may also be associated with susceptibility to TB, although the ethnic difference exists.…”
Section: Discussionmentioning
confidence: 99%
“…It suggested that the CNV was an independent risk factor for pulmonary TB in contrast with SNPs among Chinese Uygurs. However, a recent study found that there was an association of CCL3L1 copy number with TB in a northwestern Colombian population [ 31 ], but not in African and Peruvian populations [ 32 ]. All these data indicate that CNVs in some special genes may also be associated with susceptibility to TB, although the ethnic difference exists.…”
Section: Discussionmentioning
confidence: 99%
“…They observed that -403G/G and -28C/C genotypes as well as -403G allele and -28C allele were significantly more frequent in control subjects. Carpenter et al (2014) didn't find any association between CCR5 polymorphism and susceptibility to clinically active TB. Mishra et al (2012) have found no significant association between CCR5 polymorphism with either resistance or susceptibility to TB in Sahariya tribe of north central India population.…”
Section: Discussionmentioning
confidence: 88%
“…CCR5 Δ32 is a deletion of gene results in a non-functional receptor form of the chemokine receptor that is unable to bind CC chemokine ligands such as CCL5. Numerous studies have shown the association of CCL5 and CCR5 gene polymorphism and the risk of TB in various ethnic populations, but the results were controversial (Ben-Selma et al, 2011;Selvaraj et al, 2011;Carpenter et al, 2014). Therefore, the present case-control study was designed to investigate the possible association between CCL5 -403G/A (rs2107538), CCL5 -28C/G (rs2280788) and CCR5 Δ32 polymorphisms and pulmonary tuberculosis in a sample of southeast Iranian population.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The gene CCR5 is polymorphic and located within the gene cluster on chromosome 3p21.3-p24 [ 17 ]. The polymorphisms in this gene may affect the activity of the protein, thus contributing to multiple diseases, including HIV-1 infection [ 18 ], cancers [ 19 ], tuberculosis [ 20 ], atopic asthma [ 21 ] and DN [ 22 ].…”
Section: Introductionmentioning
confidence: 99%